The efficacy and safety of ginkgo terpene lactone preparations combined with antiplatelet aents in the treatment of ischemic stroke: a systematic review and meta-analysis - Xu, Hong; Zeng, Li; Liao, Li; Li, Xiaoxuan; Tang, Yan (Frontiers in Pharmacology, 2025)
BackgroundThis meta-analysis aimed to assess the efficacy and safety of ginkgo terpene lactone preparations including diterpene ginkgolides meglumine injection (DGMI) and ginkgolide injection combined with antiplatelet drugs in the treatment of ischemic stroke.MethodsWe systematically searched the randomized controlled trials(RCTs) with publication date earlier than 6 November 2024 in PubMed, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Journal Database (VIP), Chinese Biomedical Literature Database (CBM), Wanfang Database, Embase, Web of Science, ClinicalTrials.gov, and Cochrane Library. Studies were screened according to inclusion and exclusion criteria, evaluated according to criteria recommended by the Cochrane Handbook, and data were then analyzed using Stata 17 software.ResultsOf 1,079 identified studies, 27 were eligible and included in our analysis (N = 3,336 patients). The meta-analysis demonstrated that the overall response rate [RR = 1.22, 95% CI(1.17, 1.27), Z = 9.76, p < 0.01], as well as the National Institutes of Health Stroke Scale (NIHSS) score and barthel index, were significantly better in the DGMI combined treatment group compared to the antiplatelet therapy alone group. However, there was no significant difference observed between the experimental group and the control group regarding improvements in prognosis and platelet function. The studies included in the analysis reported a total of 419 adverse reactions (ADRs), with 206 occurring in the DGMI combined treatment group; furthermore, there was no significant difference in the incidence of adverse events between the two groups.ConclusionGinkgo terpene lactone preparations, when combined with antiplatelet drugs, can significantly enhance the clinical efficacy of ischemic stroke and demonstrate a favorable safety profile. This combination is a potential treatment strategy that can improve the management of IS patients and has high clinical application value.